(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Knowledge is an imperative of life that must prove its practical efficiency, overcoming the obstacles and disadvantages it encounters ideological inclinations or preferences. Human society moves, develops, progresses or regresses, depending on the contexts in which it manifests itself. It can be appreciated that each method is important from a scientific point of view, be it analytical or synthetic, and each, in turn, contributes to the analysis and deepening of knowledge of population consumption at a given moment or over a wider time horizon. The values of consumption determined by the descriptive method compared to the normed one, in the case of employees and peason families are small. The real consumption of these families is lower than what would usually exist, unlike pensioner families who, in reality, consume more than is normal for this type of family. The importance of the minimum subsistence level is great by supporting the dimensioning of poverty in a country or in a certain time and the measures that can be taken to support the population in needs.